The impact of chronic stress on cortical thickness in patients with depression - Li, Na; Li, Yong; Lu, Yueying; Zhang, Kun; Wang, Shuo; Wang, Chaomin (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the effect of chronic stress on cortical thickness in patients with depression.MethodsWe recruited 90 participants (Jan 2023-Oct 2024): 30 treatment-naive depressed patients with chronic stress (CSD group; mean age 39.1 ± 9.8 years, baseline HAMD-17 27.4 ± 4.8), 30 treatment-naive depressed patients without chronic stress (Dep group; 38.9 ± 9.6 years, HAMD 26.1 ± 4.9), and 30 age/sex-matched healthy controls (HC; 41.2 ± 10.0 years). Chronic stress was defined using the Life Events Scale (LES > 100, based on regional norms). All patients received Fluvoxamine Maleate treatment. LES scores, HAMD-17 scores, and cortical thickness (via MRI) were assessed pre-treatment and 2 months post-treatment. Depressive relapse was monitored for 12–14 months (mean 12.9 ± 1.6 months).ResultsBaseline: LES scores were CSD > Dep > HC (all P<0.05); HAMD scores were CSD≈Dep > HC (P<0.05). Compared to HC, both patient groups showed reduced baseline cortical thickness in left pars triangularis, pars opercularis, precuneus, middle temporal, and cingulate gyri, and right superior frontal, precuneus, and inferior frontal gyri (P<0.05). Crucially, the CSD group exhibited significantly greater thinning than the Dep group in these regions (P<0.05). Post-treatment (2 months): LES and HAMD scores decreased significantly in both patient groups but remained higher than HC (P<0.05). Post-treatment LES scores remained CSD > Dep (P<0.05), while HAMD scores were similar between patient groups (P>0.05). Cortical thickness increased in CSD and Dep groups but did not reach HC levels (P<0.05), and the difference between CSD and Dep thickness was no longer significant (P>0.05). The CSD group experienced significantly faster time to relapse (mean 5.4 ± 2.3 months) compared to the Dep group (8.3 ± 2.5 months; t=4.656, P<0.001).ConclusionChronic stress contributes to greater cortical thinning in depressed patients, particularly in specific frontal, temporal, parietal, and cingulate regions. Although treatment facilitates cortical thickness recovery alongside symptom improvement, individuals experiencing chronic stress relapse more quickly.